PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN RICHEESE FACTORY DI KOTA BANDUNG - Candy, Albertus; Adialita, Tania (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The purpose of this research is to analyze the influence of Service Quality on Customer Loyalty which is mediated by Richeese Factory Customer Satisfaction in Bandung City. The sampling technique uses convenience sampling which is included in non-probability sampling. The sample determined was 120 respondents. The data in this research were obtained from primary data in the form of questionnaire results and secondary data obtained from Topbrandaward, 2023. Data were analyzed through validity tests, reliability tests, classical assumption tests, simple and multiple regression tests, hypothesis tests and Sobel tests. The results of this research are: 1) Service quality has a positive and significant effect on Richeese Factory customer satisfaction in the city of Bandung, 2) Service quality has a positive effect on Richeese Factory customer loyalty in Bandung City, 3) Customer satisfaction has a positive effect on Richeese Factory customer loyalty in Bandung city, 4) Customer satisfaction plays a positive role in mediating the influence of service quality on Richeese Factory customer loyalty in Bandung City.